ESP under hypnosis: the role of induction instructions and personality characteristics - Tressoldi, Patrizio; Del Prete, Guido (The Journal of parapsychology, 2007)
In the present study, we compared directly the efficacy of two types of hypnotic induction instructions on a forced-choice clairvoyance task in a sample of participants selected for their medium to high absorption or transliminality scores. The first kind of instructions (ESP) emphasized the capacity to visualize a remote picture, freeing the mind from any thinking activity. The second kind of instructions, the out-of-body experience (OBE), emphasized leaving the body and allowing the mind to go where the target was presented. The two instructions were applied in a within-subject design to control individual differences better. In the 2 sessions of 10 trials each, the mean hit scores were: first session: M = 3.33 (SD = .65); second session: M = 2.41 (SD = .79). The mean hit score of the first session was well above MCE, π = .60; CI: .28-.91; contrast: Δπ = .10. No substantial differences were obtained with the two kinds of instructions. These data replicate the findings obtained by Del Prete and Tressoldi (2005), supporting the hypothesis that a combination of hypnosis and special induction instructions tailored for the ESP task facilitate the performance in participants with medium to high absorption or transliminality scores. En este estudio comparamos directamente la eficacia de dos tipos de instrucciones de induccion hipnotica sobre una tarea de clarividencia de respuesta limitada (forced-choice) en una muestra de participantes seleccionados por puntuaciones medianas o altas de absorcion o de transliminalidad. Las pimeras intrucciones, sobre percepcion extrasensorial (PES), enfatizaron la capacidad de visualizar una ilustracion remota liberando la mente de actividades de pensamiento. Las segundas instrucciones, sobre experiencias fuera dei cuerpo, enfatizaron salir del cuerpo y dejar la mente ir al lugar en donde se encontraba el objetivo. Las dos intrucciones fueron usadas en un diseno intra-sujeto para controlar por diferencias individuales. En las 2 sesiones de 10 ensayos cada una, el promedio de exitos fue: primera sesion: M = 3.33 (SD = .65); segunda sesion: M = 2.41 (SD = .79). E1 promedio de exitos en la primera sesion fue sobre lo esperado al azar, π = .60; CI: .28-.91; contraste: Δπ =. 10. No hubo diferencias substanciales entre las dos clases de instrucciones. Estos resultados replican los hallazgos de Del Prete y Tressoldi (2005), y apoyan la hipotesis de que una combinacion de la hipnosis y de instrucciones especiales de induccion adaptadas para la prueba de PES facilitan el desempeno en los participantes con puntuaciones medianas o altas de absorcion y transliminalidad. In der vorliegenden Studie wurde ein direkter Vergleich der Wirksamkeit zwischen zwei Arten hypnotischer Induktionsinstruktionen bei einem Hellsehtest mit begrenzten Wahlmoglichkeiten vorgenommen. Die Stichprobe bestand aus ausgewahlten Probanden, die mittlere bis hohe Treffer-scores bei ,Absorption' oder ,Transliminalitat' erzielten. Die erste Versuchsinstruktion (ASW) betonte die Fahigkeit, ein raumlich entferntes Bild zu visualisieren, indem sich der Geist von jeder reflektierenden Aktivitat frei machen sollte. Mittels der zweiten Instruktion (Ausserkorperliche Erfahrung, AKE) sollte der Korper verlassen werden und der Geist sollte sich an diejenige Stelle begeben, an der sich das Zielobjekt befand. Die beiden Instruktionen wurden der jeweils gleichen Versuchsperson gegeben, um individuelle Unterschiede besser kontrollieren zu konnen. In den beiden Sitzungen mit jeweils zehn Versuchsdurchgangen wurden folgende mittlere Trefferquoten erzielt: Erste Sitzung : M = 3.33 (SD = .65); zweite Sitzung: M = 2.41 (SD = .79). Die mittlere Trefferquote der ersten Sitzung lag deutlich uber der Zufallserwartung MCE, π = .60; CI: .28-.91; Kontrast: Δπ = .10. Die beiden Instruktionsarten fuhrten zu keinen wesentlichen Unterschieden. Die Befunde replizieren die Ergebnisse von Del Prete und Tressoldi (2005) und unterstutzen die Hypothese, dass eine Kombination von Hypnose mit speziell auf eine ASW-Aufgabe zugeschnittenen Versuchinstruktionen die Trefferleistung bei Probanden begunstigen, die bei ,Absorption' oder ,Transliminalitat' mittlere bis hohe Trefferscores erzielen. Dans la presente etude, nous comparons directement l'efficacite de deux types d'inductions hypnotiques sur une tache de clairvoyance a choix force, avec un groupe de participants selectionnes pour leurs scores moyens et eleves en absorption et en transliminalite. Le premier type d'instructions (PES) met en avant la capacite de visualiser une image a distance, liberant l'esprit de toutes les activites de pensee. Le second type d'induction, la sortie hors du corps (OBE), met l'accent sur le fait de quitter son corps et de permettre a son esprit d'aller la oU la cible est presentee. Les deux inductions ont ete employees dans un dispositif avec des sujets permettant de mieux controler les differences individuelles. Dans les 2 sessions de 10 essais chacune, le taux de score moyen fut : premiere session : M = 3.33 (SD = .65); seconde session: M = 2.41 (SD = .79). Le score moyen a la premiere session fut bien au dessus de ce qu'on pouvait attendre du hasard, n = .60; CI: .28-.91; contraste: Δπ =. 10. Aucune differente substantielle n'a ete obtenue avec les deux types d'induction. Ces donnees repliquent les decouvertes obtenues par Del Prete & Tressoldi (2005), supportant l'hypothese qu'une combinaison d'hypnose et d'inductions specifiquement crees pour les PES facilite la performance des participants ayant des scores moyens et eleves d'Absorption et de Transliminalite.